Electrospun fish gelatin fibrous scaffolds with improved bio-interactions due to carboxylated nanodiamond loading. Issue 116 (5th November 2015) - Serafim, A.; Cecoltan, S.; Lungu, A.; Vasile, E.; Iovu, H.; Stancu, I. C.
Abstract : This work emphasizes the potential of COOH-functionalized nanodiamond (NDs) particles to improve bio-interactions when embedded into fish gelatin electrospun fibers. Abstract : Nanotechnology and biomimicry represent appealing but still underexploited techniques to develop innovative scaffolds with ECM-inspired features for tissue engineering. In the present work we have investigated the potential of a combination of two designed elements to trigger enhanced bio-interactions with bone regeneration potential: COOH-functionalized nanodiamond particles (COOH-NDPs) have been loaded for the first time into electrospun fish gelatin hydrogel fibers thus generating nanocomposite fibrous scaffolds with interconnected porosity. When compared to control fish gelatin fibers, no significant modification of the mineralization capacity in acellular simulated body fluid has been evidenced by micro-structural and spectroscopic investigations, for fibers with COOH-NDPs content ranging from 0.25% to 1%. It is important to mention that, following Ca/P alternate incubation, nano-apatite crystals were preferentially developed and firmly adhered on the fiber regions in the proximity of COOH-NDPs, as proven by transmission electron microscopy (TEM). Significant mineralization occurred in the culture media in the presence of MG63 osteoblast-like cells and seems to be directly stimulated by the presence of the nanoparticles. Altogether, these findings emphasize the ability of NDPs to enhance, when immobilized in gelatin fibers and exposed to specific media, the formation of apatite. It was also noticed that the number of adherent MG63 cells, their morphology and spreading were improved by increasing the amount of NDPs in the fibers (fluorescence and scanning electron microscopy). This work successfully proves the potential of such nanocomposite fibers to find applications in bone regeneration.